Spectrophotometric evaluation of dental bleaching under orthodontic bracket in enamel and dentin - Lunardi, Nádia; Correr, Américo Bortolazzo; Rastelli, Alessandra Nara de Souza [UNESP]; Lima, Débora Alves Nunes Leite; Consani, Rafael Leonardo Xediek (Medicina Oral, S.L., 2014)
Aware of the diffusion capacity of bleaching in the dental tissues, many orthodontists are subjecting their patients to dental bleaching during orthodontic treatment for esthetic purposes or to anticipate the exchange of esthetic restorations after the orthodontic treatment. For this purpose specific products have been developed in pre-loaded whitening trays designed to fit over and around brackets and wires, with clinical efficacy proven. Objective: The objective of this study was to evaluate, through spectrophotometric reflectance, the effectiveness of dental bleaching under orthodontic bracket. Material and Methods: Thirty-two bovine incisors crown blocks of 8 mm x 8 mm height lengths were used. Staining of tooth blocks with black tea was performed for six days. They were distributed randomly into 4 groups (1-home bleaching with bracket, 2- home bleaching without bracket, 3- office bleaching with bracket, 4 office bleaching without bracket). The color evaluation was performed (CIE L * a * b *) using color reflectance spectrophotometer. Metal brackets were bonded in groups 1 and 3. The groups 1 and 2 samples were subjected to the carbamide peroxide at 15%, 4 hours daily for 21 days. Groups 3 and 4 were subjected to 3 in-office bleaching treatment sessions, hydrogen peroxide 38%. After removal of the brackets, the second color evaluation was performed in tooth block, difference between the area under the bracket and around it, and after 7 days to verified color stability. Data analysis was performed using the paired t-test and two-way variance analysis and Tukey’s. Results: The home bleaching technique proved to be more effective compared to the office bleaching. There was a significant difference between the margin and center color values of the specimens that were subjected to bracket bonding. Conclusions: The bracket bond presence affected the effectiveness of both the home and office bleaching treatments.
Keywords: Tooth bleaching; Spectrophotometry; Orthodontics